2019
DOI: 10.1111/odi.13251
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐related outcomes in Sjögren syndrome treated with stimulants of salivary secretion: Randomized clinical trial

Abstract: Objectives To investigate the impact of gustatory stimulants of salivary secretion (GSSS) on Sjögren's syndrome patients’ self‐perception of xerostomia, oral health‐related quality of life (OHRQoL) and salivary secretion. Methods A total of 110 Sjögren's syndrome patients were randomly allocated to be treated with either a malic acid lozenge or a citric acid mouthwash and then crossed over. Before and after the interventions, the Xerostomia Inventory 5 (SXI‐5‐PL) and the Oral Health Impact Profile (OHIP‐14‐PT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
(87 reference statements)
0
10
0
1
Order By: Relevance
“…In a randomized clinical trial, the effect of malic acid on OHRQoL of patients with SS was tested. The largest improvement was recorded for psychological pattern [29]. Another study in patients with RA found correlations between disease activity and the pattern of psychosocial impact [17].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In a randomized clinical trial, the effect of malic acid on OHRQoL of patients with SS was tested. The largest improvement was recorded for psychological pattern [29]. Another study in patients with RA found correlations between disease activity and the pattern of psychosocial impact [17].…”
Section: Discussionmentioning
confidence: 89%
“…For a deeper understanding, the subscales of OHRQoL can be considered additionally. Because five studies did not compare subscales to a healthy control [14,17,28,29,32], and different subscales were applied, the comparability is limited. However, some interesting information can be derived from the findings: In the vast majority of studies with a control group (5/6), a significant effect of the subscale "physical disability" was confirmed without any predominant manifestation in one of the included diseases [8,11,20,30,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies in the literature evaluating the relationship between various systemic and autoimmune diseases and saliva pH. 35,36 Mumcu et al 37 reported in their study on patients with Behcet's disease that saliva pH was lower compared to the control group. Additionally, Loyola et al 38 reported in their study on Systemic Lupus Erythematosus (SLE) patients that the stimulated saliva flow rate and saliva pH values were lower than the control group, which caused an increase in the DMFT index values.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the injection of a depot formulation of rapamycin into the lacrimal glands of a murine model of sialoadenitis was able to reduce inflammation and improve tear production with significantly lower amounts of drug, compared to systemic administration (89). A randomised clinical trial comparing the effect of citric acid solution and malic acid lozenges as salivary stimulants confirmed their ability to improve secretion and oralrelated quality of life, with the lozenges being more effective than the solution, maybe due to their stronger mechanical stimulation (90). Nevertheless, the increase of salivary secretion induced by pilocarpine does not seem to be effective in improving periodontal conditions, at least in the short period (91).…”
Section: New Insights In Ss Treatmentmentioning
confidence: 99%